Mastery of primary school teacher pedagogy competency in curriculum 2013 implementation in Indonesia - Bentri, Alwen (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2017)
This study aims to examine how the mastery of teacher pedagogy competence in the implementation of the curriculum 2013 in the Padang city. This research uses a quantitative approach by using purposive sampling technique. Piloting school in question is spread over a number of districts in Padang with a sample of 45 peoples. The results showed that in the mastery of pedagogy competence as 52.00% of teachers have been ready for the implementation of the curriculum 2013. Traced deeper through an interview obtained results that are a weakness of teachers less able in; (1) managing the class, (2) enabling students trough the learning process, (3) varying the learning strategy. It is recommended that the training provided to teachers more intensive and sustainable so that the mastery of pedagogical competence is more optimal.